Sportmedizinische Aspekte des Triathlons - Leonhard, E. C. (1998)
The main object of this study was to increase the efficiency of physical exercise by stepping up the intensity Of workout units, especially during the initial period of seasons. 8 athletes of triathlon of different levels of performance took part in this project. Exact records were kept about their training and changes of performance were checked, evaluated and analyzed continuously by means of bike-ergometers, respectively field tests. Moreover in the course of the study the following blood parameters were controlled regularly: Electrolytes, trace elements, cholesterol, MCV and haemoglobin. Towards the end of the training year it turned out that the intensity, as carried out in this study, was too vigorous and it showed that because of this the increase of performance acquired in the course of the year, would not be kept up till the competition period.